2015
DOI: 10.1515/msp-2015-0078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial Co replacement by Fe in Sr0.775Y0.225CoO3-δ on its magnetic property, oxygen deficiency and crystal structure

Abstract: A study has been conducted on the effects of partial, 10 % Co substitution by Fe in the perovskite Sr0.775Y0.225CoO3-δ compound. The XRD data show that the resulted samples of Fe-free and Fe-doped compounds exhibit good 314 single phase quality with a tetragonal I4/mmm crystal structure. The measured M-T curves display the typical feature of ferromagnetic (FM) transition at 335 K for the Fe-free sample, while showing significantly degraded FM ordering for the 10 % Fe-doped sample. The oxygen deficiency determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The FC curves had the highest peak at 267 K. As the temperature continues to decrease, a ferromagnetic-antiferromagnetic transition occurs, and a G -type antiferromagnetic phase is generated ( Lindberg et al, 2006 ). The separation of the ZFC and FC curves at low temperature indicates that spin-glass state-like components may be present ( Motohashi et al, 2005 ; Sutjahja et al, 2015 ; Guo et al, 2018 ; Srivastava et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The FC curves had the highest peak at 267 K. As the temperature continues to decrease, a ferromagnetic-antiferromagnetic transition occurs, and a G -type antiferromagnetic phase is generated ( Lindberg et al, 2006 ). The separation of the ZFC and FC curves at low temperature indicates that spin-glass state-like components may be present ( Motohashi et al, 2005 ; Sutjahja et al, 2015 ; Guo et al, 2018 ; Srivastava et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, perovskite cobalt oxide of SrCoO 3 − δ is very interesting, since it can be used as a cathode material of solid oxide fuel cells [7] and active material in spintronic devices [8]. It has also been found that the structural and magnetic properties of SrCoO 3 − δ sensitively depend on O 2 and applied pressure.…”
Section: Introductionmentioning
confidence: 99%